Torque ripple reduction of brushless DC motor based on adaptive input-output feedback linearization. (September 2017) - Shirvani Boroujeni, M.; Markadeh, G.R. Arab; Soltani, J.
Abstract: Torque ripple reduction of Brushless DC Motors (BLDCs) is an interesting subject in variable speed AC drives. In this paper at first, a mathematical expression for torque ripple harmonics is obtained. Then for a non-ideal BLDC motor with known harmonic contents of back-EMF, calculation of desired reference current amplitudes, which are required to eliminate some selected harmonics of torque ripple, are reviewed. In order to inject the reference harmonic currents to the motor windings, an Adaptive Input-Output Feedback Linearization (AIOFBL) control is proposed, which generates the reference voltages for three phases voltage source inverter in stationary reference frame. Experimental results are presented to show the capability and validity of the proposed control method and are compared with the vector control in Multi-Reference Frame (MRF) and Pseudo-Vector Control (P-VC) method results. Highlights: In this paper at first, a mathematical expression for torque ripple harmonics is done. For a non-ideal BLDC motor with known harmonic contents of back-EMF, calculation of desired reference current amplitudes, which are required to eliminate some selected harmonics of torque ripple, is done. A new Adaptive Input-Output Feedback Linearization (AIOFBL) control method is proposed to inject the harmonic current to the motor windings. Experimental results are presented to show the capability and validity of the proposed control method. Comparison of AIOFBL method with harmonic injection and pseudo- vector control and vector control in Multi reference frame methods is done using a DSP-based experimental setup.